Fenomena Pelanggaran Lalu Lintas: Telaah atas Tiga Paradigma Sosiologi dan Rekomendasi Kebijakan - Indra Setia Bakti; Khairul Amin; M. Husen (RESAM Jurnal Hukum, 2023)
Traffic rules are crucial in maintaining safety, order, and the smooth traffic flow. However, observations have shown that people react to them differently, from adhering to the rules to breaking them. This article analyzes the phenomenon of traffic violations using three sociological paradigms: the social facts paradigm, the social definition paradigm, and the social behavior paradigm. The research employs a literature review methodology. The study emphasize the importance of elaborating on these three sociological paradigms to provide a comprehensive approach to addressing traffic violation issues. The government should consider strengthening social norms, increasing awareness and motivation, as well as implementing strict penalties in formulating and implementing policies related to traffic rules. Meanwhile, it is also important to encourage cooperation between the government, law enforcement agencies, educational institutions, civil society, and the private sector to reduce traffic violations and improve traffic safety.